Tax Enforcement Strategy: The Antidote to Non-Tax Compliance in North-West Nigeria - Abdulrasaq , Mustapha; Babatunde, Abdullahi Adio (Journal of Business Management and Accounting, 2024)
Voluntary SME tax compliance has been of great interest to governments all over the world, given their unimpressive contribution to total tax revenue. This is even more so in Nigeria where the culture of tax compliance among SMEs can be described as poor, requiring innovative enforcement strategies. This study examined the extent to which tax enforcement strategies served as antidote to non-tax compliance in the North-West Nigeria. The study collected quantitative data from 345 randomly and purposively selected SMEs owners duly registered in North-west, Nigeria. The data was subjected to both descriptive and inferential analysis through techniques of central tendency and multiple regressions. Results revealed that three tax enforcement strategies: Use of tax clearance certificate (β=0.024 < 0.003), grant of tax amnesty (β=0.025< 0.020), and imposition of tax penalty (β = 0.013 < 0.014) have significant positive influence on degree of tax compliance among SMEs in the North-West Nigeria. Given the significant statistical evidence, this research inferred and concluded that deployment of both punitive (tax penalty) and persuasive measures (tax clearance certificate and tax amnesty) serve as antidote to non-tax compliance among the SMEs in the North-West, Nigeria. The study shows that tax compliance across informal sectors can be enhanced beyond the use of legal means. In essence, governments have the leverage of achieving increase in tax revenue in the informal sector through multiple strategies of motivation and punishment as implicitly emphasized in the theory of tax morale and deterrence theory.